Respuesta :
2x-y = -4 OR y = 2x+4
-3x+y=44
-3x + (2x+4)= 44
-x = 40
x = -40 and y = -76 (2*-40 + 4)
c-5d=2 OR c = 5d + 2
2c + d =4
2(5d+2) + d = 4
11d = 0
d = 0 and c = 2
-3x+y=44
-3x + (2x+4)= 44
-x = 40
x = -40 and y = -76 (2*-40 + 4)
c-5d=2 OR c = 5d + 2
2c + d =4
2(5d+2) + d = 4
11d = 0
d = 0 and c = 2
2x-y = -4 OR y = 2x+4
-3x+y=44
-3x + (2x+4)= 44
-x = 40
x = -40 and y = -76 (2*-40 + 4)
c-5d=2 OR c = 5d + 2
2c + d =4
2(5d+2) + d = 4
11d = 0
d = 0 and c = 2
-3x+y=44
-3x + (2x+4)= 44
-x = 40
x = -40 and y = -76 (2*-40 + 4)
c-5d=2 OR c = 5d + 2
2c + d =4
2(5d+2) + d = 4
11d = 0
d = 0 and c = 2